Fractal-Based Generative Design of Structural Trusses Using Iterated Function System. Issue 4 (December 2014) - Rian, Iasef Md; Sassone, Mario
The purpose of this study is to apply the notion of fractal geometry in designing structural roof trusses. Fractal geometry, commonly characterized by the features of recursive self-similarity, is considered as a rule-based geometric system that can be generated by using the process of the Iterated Function System (IFS). Lattice configurations of conventional trusses generally show some extend of 'self-similarity' features that loosely and sometimes closely resemble with the properties of fractal shapes. The typical configurations of these regular trusses are strategically designed to provide adequate strength and stability to the structures for carrying enough vertical and wind loads. This paper, using the Iterated Function System based on Barnsely's contraction mapping as a generative design method, proposes a new family of truss designs that follow the concept of fractal geometry. The Hausdorff dimensions and the Box Counting dimensions are evaluated to measure the fractality and detailness of the lattices of proposed fractal-based trusses. It also briefly investigates their mechanical properties for analyzing their practical feasibility in construction.